2013
DOI: 10.1093/nar/gkt467
|View full text |Cite
|
Sign up to set email alerts
|

A novel interplay between the Fanconi anemia core complex and ATR-ATRIP kinase during DNA cross-link repair

Abstract: When DNA replication is stalled at sites of DNA damage, a cascade of responses is activated in the cell to halt cell cycle progression and promote DNA repair. A pathway initiated by the kinase Ataxia teleangiectasia and Rad3 related (ATR) and its partner ATR interacting protein (ATRIP) plays an important role in this response. The Fanconi anemia (FA) pathway is also activated following genomic stress, and defects in this pathway cause a cancer-prone hematologic disorder in humans. Little is known about how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 62 publications
(66 reference statements)
3
45
0
Order By: Relevance
“…4,59 Interestingly while MMC elicits the checkpoint, ATR activation is via the Fanconi anemia core complex rather than the canonical pathway involving Rad17. [59][60][61] Thus, our findings raise the possibility that the action of CST is somehow linked to a specific aspect of ATR signaling. We previously showed that STN1 depleted cells exhibit a normal ATR response to HU treatment as the level of Chk1 phosphorylation is similar to that of control cells as is the rate of Chk1 dephosphorylation and loss of RPA foci after HU release.…”
Section: Discussionmentioning
confidence: 70%
“…4,59 Interestingly while MMC elicits the checkpoint, ATR activation is via the Fanconi anemia core complex rather than the canonical pathway involving Rad17. [59][60][61] Thus, our findings raise the possibility that the action of CST is somehow linked to a specific aspect of ATR signaling. We previously showed that STN1 depleted cells exhibit a normal ATR response to HU treatment as the level of Chk1 phosphorylation is similar to that of control cells as is the rate of Chk1 dephosphorylation and loss of RPA foci after HU release.…”
Section: Discussionmentioning
confidence: 70%
“…S1C and S4A). Rad17 promotes Chk1 phosphorylation, which is a marker of replication checkpoint activation, in association with Rad9-Rad1-Hus1, TopBP1, and ATR-ATRIP, whereas it does not affect the monoubiquitination of FANCD2 [25,30]. RECQL5 / RAD17 KO cells showed higher sensitivity to CDDP than single mutants (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The recruitment of ATRIP was reported to be essential for FANCD2 monoubiquitination and FANCI phosphorylation, and the latter is catalyzed by ATR kinase [70]. The FA core complex E3 was found to also enhance the binding of ATRIP to the damaged chromatin site [71]. Together, FANCM, FANCW and other FA players certainly play critical roles in the sensor phase upon stalled replication forks.…”
Section: Fa Signaling and Master Regulators Of Cellular Stress Rementioning
confidence: 99%